1989
DOI: 10.1073/pnas.86.22.8852
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity suggests tumor suppressor gene responsible for primary hepatocellular carcinoma.

Abstract: Primary hepatocellular carcinoma (PHC), epidemiologically associated with chronic hepatitis B virus (HBV) infection, has historically been felt to be caused by the activation or introduction of an oncogene. However, transforming sequences from human PHC have not been reproducibly isolated. In this paper, evidence is presented that suggests PHC may result instead from the loss of an anti-oncogene. Seven of 12 human primary liver tumors tested against a panel of restriction fragment length polymorphisms (RFLPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(96 citation statements)
references
References 45 publications
3
91
2
Order By: Relevance
“…A tumour-suppressor gene relevant for HCC development has already been suspected at this location from several LOH studies (frequency: 17-77%) (Buetow et al, 1989;Zhang et al, 1990;Konishi et al, 1993;Yeh et al, 1996;Chou et al, 1998). A common chromosomal breakpoint mapped to 4q has also been found in 4 out of 50 HCCs (Pasquinelli et al, 1988) as well as an HBV integration site in an HCC at 4q32.1.…”
Section: Discussionmentioning
confidence: 93%
“…A tumour-suppressor gene relevant for HCC development has already been suspected at this location from several LOH studies (frequency: 17-77%) (Buetow et al, 1989;Zhang et al, 1990;Konishi et al, 1993;Yeh et al, 1996;Chou et al, 1998). A common chromosomal breakpoint mapped to 4q has also been found in 4 out of 50 HCCs (Pasquinelli et al, 1988) as well as an HBV integration site in an HCC at 4q32.1.…”
Section: Discussionmentioning
confidence: 93%
“…LOH, including the interval we have defined, has also been reported in cases of carcinoma of the oesophagus (Hu et al, 2000;Rumpel et al, 1999), cervix (Mitra et al, 1994) and liver (Bluteau et al, 2002;Buetow et al, 1989). In addition, a comparative genomic hybridization study of small cell cancer of the lung revealed loss of the 4q11 -q23 region in 86% of cases (Petersen et al, 1997) and the same technique has revealed the loss of chromosome 4q in breast (Tanner et al, 1998) colon (Arribas et al, 1999) and prostate (Virgin et al, 1999) carcinoma.…”
Section: Allele Lost Allele Retained Not Informative Not Informativementioning
confidence: 91%
“…The alteration of 1p as an early event in HCC has been implicated previously. 33 Although genetic alterations in 4q in HCC have been documented, 14,17,33,37,38 their relevance to the development and stage of HCC has not been determined. The role of genetic alteration in the 4q and 4q28 region in particular on the initiation and progression of HCC should be further examined.…”
Section: Discussionmentioning
confidence: 99%